Comparing The Efficacy of Incision and Drainage (I & D) Vs. Ultrasound-Guided Needle Aspiration (UGNA) Methods to Manage Puerperal Breast Abscess: Efficacy of Incision and Drainage Vs Ultrasound-Guided Needle Aspiration - Ali, Huda; Aziz, Munazzah; Iftikhar, Maryam; Munawar, Sidra; Qurban, Sana (Pakistan Journal of Health Sciences, 2024)
Puerperal breast abscess poses a significant challenge in clinical care as they refer to painful, inflamed lesions that occur in lactating women stemming from untreated mastitis complications and often require expedited intervention to alleviate pain and avert adverse effects. The management of puerperal breast abscess is a medical dilemma that ranges from non-invasive therapy to surgical intervention. Objective: To compare the efficacy of ultrasound-guided needle aspiration (UGNA) and incision and drainage (I & D) in the management of puerperal breast abscess. Method: A systematic review was performed based on Preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Epidemiological studies published from 2013 to 2023 were included from five databases based on the presence of qualitative and quantitative data. Results: UGNA demonstrated efficacy compared to I & D. The observed cure rate of UGNA was 83% to 92% and an acceptable failure rate of 17.5% was associated with more than one aspiration. Conversely, the I & D method was associated with a prolonged healing period, pain, interrupted breastfeeding, more visits to the hospital, regular wound dressing, scarring, and fistula development however, more suitable for larger abscesses. Conclusions: The UGNA method appears to be an effective first-line treatment for managing unilocular puerperal breast abscesses, particularly those smaller than 5 cm, due to its shorter healing time, fewer hospital visits, and better cosmetic outcomes compared to traditional surgical methods. However, future research on large-scale RCTs with extended monitoring is needed